Reconstitution of an active arginine deiminase pathway in mycoplasma pneumoniae M129 - Rechnitzer, Hagai; Rottem, Shlomo; Herrmann, Richard (Infection and immunity, 2013)
Some species of the genus Mycoplasma code for the arginine deiminase pathway (ADI), which enables these bacteria to produce - ATP from arginine by the successive reaction of three enzymes: arginine deiminase - (ArcA), ornithine carbamoyltransferase (...